Governing in Fragments: Coalition Politics and Power-Sharing in India - Tirkey, C. Anupa (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Coalition politics has become an enduring feature of India’s multi-party democratic framework, reflecting the country’s deep social diversity and its evolving electoral landscape. Since the decline of single-party dominance in the late twentieth century, political alliances have emerged as the central mechanism for forming and sustaining governments at both the national and state levels. This paper examines the historical evolution, structural mechanisms, and governance implications of coalition politics in India, focusing on the interplay between stability and representation. It analyses the formation strategies of pre-poll and post-poll alliances, the negotiation of power-sharing arrangements, and the institutional tools employed to maintain coalition unity. Drawing on case studies from both national and state contexts, the study highlights the factors that contribute to coalition stability, such as leadership style, ideological compatibility, and effective conflict resolution. It also explores the challenges posed by fragmented mandates, regional demands, leadership centrality, and ethical concerns in alliance politics, while recognising the positive role of coalitions in enhancing inclusivity, strengthening federalism, and checking the concentration of power. The paper concludes by proposing institutional and electoral reforms aimed at improving coalition stability without undermining representation. By situating coalition politics within India’s democratic and federal framework, the study offers insights into how alliances can evolve from arrangements of political necessity into durable platforms for inclusive and effective governance.